Aberrant Functional Connectivity between the Amygdala and the Temporal Pole in Drug-Free Generalized Anxiety Disorder - Li, Wei; Cui, Huiru; Zhu, Zhipei; Kong, Li; Guo, Qian; Zhu, Yikang; Hu, Qiang; Zhang, Lanlan; Li, Hui; Li, Qingwei; Jiang, Jiangling; Meyers, Jordan; et al. (Frontiers in Human Neuroscience, 2016)
The amygdala and the dorsolateral prefrontal cortex (DLPFC) play important roles in “emotion dysregulation,” which has a profound impact on etiologic research of generalized anxiety disorder (GAD). The present study analyzed both eyes-open and eyes-closed resting state functional MRI (rs-fMRI) of 43 subjects (21 GAD patients with medicine free and 22 matched healthy controls). The amygdala and the DLPFC were defined as regions of interest (ROI) to analyze functional connectivity (FC) in GAD patients compared with healthy controls. The main findings revealed GAD patients had increased FC between the amygdala and the temporal pole compared to healthy controls, which was found in both eyes-open and eyes-closed rs-fMRI. And altered FC between the ROIs and brain regions that mainly belonged to the default mode network (DMN) were found. These findings suggest that the abnormal FC between the amygdala and the temporal pole may contribute to the pathophysiology of GAD, and provide insights into the current understanding of the emotion dysregulation of anxiety disorders.